Cardiac Emergency Prevention Through Personal and Environmental Factors (Medico Legal Update, 2020)
Cardiovascular disease is the number one cause of death for non-communicable diseases. There are many types of cardiovascular disease, but the most common and well-known one is Coronary Heart Disease. Those who are diagnosed with coronary heart disease need to always be vigilant since it is highly possible for them to experience the cardiac emergency at any time, which can cause death. This study aims to determine how the efforts to prevent coronary heart disease patients against cardiac emergency through personal and environmental factors. The results of this study are expected to improve the quality of health services in coronary heart disease patients and increase the efforts of preventing cardiac emergencies in the patients with coronary heart disease independently. There were 118 patients with a medical diagnosis of coronary heart disease as the sample of this study. It utilizes the observational analytic method with cross sectional research design. The analysis technique used was variance or component-based Structural Equation Modeling (SEM). The results showed that there were coronary heart disease patients who had suffered from the disease for more than 1 (one) year (87.3%), had comorbidities: hypertension or diabetes mellitus (85.6%), had experienced a chest pain (79.7%), had a hereditary factor of heart disease (69.5%), and had a healthy lifestyle (69.9%). The results of the structural model analysis between personal factors and environmental factors indicate that there is a significant influence on preventing the cardiac emergencies.